Words that reflect new political realities: translating from Ukrainian into English - Галапчук-Тарнавська, Олена Михайлівна; Чарікова, Ірина; Halapchuk-Tarnavska, Olena M.; Charikova, Iryna (Кіровоградський державний педагогічний університет імені Володимира Винниченка, 2016)
У статті запропоновано способи перекладу українських політичних реалій, які з’явилися в словниковому складі останнім часом. Проаналізовано корпус лексичних сполучень, отриманих з сучасних англомовних Інтернет-видань The Wall Street Journal, The Guardian, The New York Times and Newsweek. The article deals with the ways of rendering the meaning of nationally biased units of lexicon that appeared due to the political events in Ukraine in 2013-2016. The research has been made on the basis of the articles taken from the English Internet media The Wall Street Journal, The Guardian, The New York Times and Newsweek.
Keywords: nationally biased units of lexicon; equivalence; ways of translating; політичні реалії; способи перекладу; еквівалентність